Flowering Development of Longan (Dimocarpus longan Lour) ‘Diamond river’ - Pining Suwardining Tyas; Dwi Setyati; Umiyah Umiyah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
‘Diamond river’ is introduction plant that cultivated in Indonesian. Development of longan flower divided into eight stadium during 28 days. First and second stadium is the induction phase that lasts for 8 days, this phase is characterized by a change in color of the leaves become older by using the Munsell color charts for plant tissues indicate the scale of 7.5 GY (4/4) to GY 7.5 scale (3\2). Third stadium is the phase of flower initiation occurred by day eigth. Initiation stage appearance were showed by merristem axilar, which will form part of primordial flower. Fourth to seventh stadium are phase that a differentiation occurred on day 12 to day 24. Differentiation phase showed the development in suitable with the typical angiosperms are sepals, stamens, petals and pistils. Eighth stadium is the phase of anthesis occurred on day 28. In the phase of anthesis, flowers have undergone a process of pollination and fertilization. Keywords: Development, Diamond river, Flowering, stadium